'Our' Community: Corporate Social Responsibility, Neoliberalisation, and Mining Industry Community Engagement in Rural Australia. (February 2014) - Mayes, Robyn; McDonald, Paula; Pini, Barbara
This paper addresses contemporary neoliberal mobilisations of community undertaken by private corporations. It does so by examining the ways in which the mining industry, empowered through the legitimising framework of corporate social responsibility, is increasingly and profoundly involved in shaping the meaning, practice, and experience of 'local community'. We draw on a substantial Australian case study, consisting of interviews and document analysis, as a means to examine 'community-engagement' practices undertaken by BHP Billiton's Ravensthorpe Nickel Operation in the Shire of Ravensthorpe in rural Australia. This engagement, we argue, as a process of deepening neoliberalisation simultaneously defines and transforms local community according to the logic of global capital. As such, this study has implications for critical understandings of the intersections among corporate social responsibility, neoliberalisation, community, and capital.